2020
DOI: 10.21203/rs.2.15953/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptome-wide map of m6A circRNAs identified in a rat model of hypoxia mediated pulmonary hypertension

Abstract: Background: Hypoxia mediated pulmonary hypertension (HPH) is a lethal disease and lacks effective therapy. CircRNAs play significant roles in physiological process. Recently, circRNAs are found to be m 6 A-modified. The abundance of circRNAs was influenced by m 6 A. Furthermore, the significance of m 6 A circRNAs has not been elucidated in HPH yet. Here we aim to investigate the transcriptome-wide map of m 6 A circRNAs in HPH. Results: Differentially expressed m 6 A abundance was detected in lungs of HPH rats.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 28 publications
(72 reference statements)
1
15
0
Order By: Relevance
“…Several studies have revealed that m 6 A modification is involved in different diseases, including pulmonary hypertension, rheumatoid arthritis, type 2 diabetes and acute myeloid leukemia 17–20 . Moreover, further studies on the biological functions of m 6 A modification related protein in lung cancer have been reported in recent years.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several studies have revealed that m 6 A modification is involved in different diseases, including pulmonary hypertension, rheumatoid arthritis, type 2 diabetes and acute myeloid leukemia 17–20 . Moreover, further studies on the biological functions of m 6 A modification related protein in lung cancer have been reported in recent years.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have revealed that m 6 A modification is involved in different diseases, including pulmonary hypertension, rheumatoid arthritis, type 2 diabetes and acute myeloid leukemia. [17][18][19][20] Moreover, further studies on the biological functions of m 6 A modification related protein in lung cancer have been reported in recent years. For example, m 6 A demethylase ALKBH5 (m 6 A eraser) has been shown to inhibit tumor growth and metastasis by reducing YTHDFs-mediated YAP expression and inhibit miR-107/ LATS2-mediated YAP activity in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension is a major risk factor for CVD, and researchers have recently disclosed that epitranscriptomic mechanism of m6A plays a critical role in hypertension. 48 The global level of m6A methylation is reduced in spontaneously hypertensive rat pericytes 49 and hypoxia mediated pulmonary hypertension, 50 and the m6A is distributed mainly in the coding sequence region, 3′UTR and 5′UTR of mRNAs. 49 m6A circXpo6 and m6A circTmtc3 are downregulated in pulmonary hypertension, moreover, m6A connects with circRNA-miRNA-mRNA network to affect the development of pulmonary hypertension.…”
Section: Hypertensionmentioning
confidence: 99%
“…Overexpression of hsa_circ_0029589 or inhibition of METTL3 can significantly increase the expression of hsa_circ_0029589 and reduce macrophage apoptosis [146]. Increased m 6 A abundance in hypoxia mediated pulmonary hypertension (HPH) reduces the total circRNAs abundance in hypoxia in vitro [147]. M 6 A affects the co-expression network of circRNA-siRNA-mRNA during hypoxia.…”
Section: Immune Responsementioning
confidence: 99%